Fairness of Health Financing before and after Introduction of Iranian Health Sector Evolution Plan: A Case Study - Soraya Nouraei Motlagh; Banafsheh Darvishi; Payam Haghighatfard; Mohammad-Hasan Imani-Nasab (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Since out-of-pocket payments of household are a serious obstacle to the equitable utilization of health services, paying attention to the direct payment of households and, consequently, incidence of catastrophic health expenditures should always be considered in the planning and policy-making of health services. Iranian Health Sector Evolution Plan (HSEP) has been implemented since 2014, aiming at achieving universal coverage of health services and reducing the amount of out-ofpocket payments as a percentage of total health expenditures. Aim: To measure the fairness of health care financing and to identify incidence rate of catastrophic health expenditures and it's most important determinants before and after implementing the HSEP among households in one province of Iran (Lorestan). Materials and Methods: The study population of present crosssectional research was Lorestan households whose information was collected by a three-stage randomized cluster sampling method by the Statistics Center of Iran during 4/2012-3/2015. For data analysis, Logit’s regression model using Stata14 software was performed. Results: Based on the findings between 4/2012 and 3/2015, the incidence rate of Catastrophic Health Expenditure (CHE) reduced from 6.7 to 4.34; Fairness Financial Contribution Index (FFCI) varied from 0.66 to 0.74 and percentage of poverty due to health expenditure varied from 1.96% to 0.28%. The most important determinants of facing catastrophic health expenditure are economic status of households, location of households (urban or rural), and number of people over the age of 65 and under the age of 5 in the household, age and sex of household head and insurance status of households. The use of health care also showed a significant relationship with the incidence of catastrophic health expenditure. Conclusion: After implementing Iranian HSEP, the incidence of CHE and the percentage of poverty caused by health expenditure at the level of households were reduced to some degree, and fairness financial contribution index improved. The finding of this study will help health policymakers to identify factors increasing the likelihood of household exposure to catastrophic health expenditure, and based on these factors, to review and revise the programs implemented within the framework of Iranian HSEP and adopt appropriate policies to promote the protection of households against catastrophic health expenditure.